Efektifitas layanan e-filing terhadap Wajib Pajak Orang Pribadi di Kantor Pelayanan Pajak Pratama Malang Selatan - Saman Abdul Aziz; Gella Intan Adestya (Jurnal Akuntansi dan Perpajakan, 2020)
This study aims to evaluate e-filing services by tax authorities to individual taxpayers, know the level of effectiveness based on the data of effective individual taxpayers who use e-filing, and know the effectiveness of the target and the realization of the use of e-filing whether it has been realized properly. Data collection techniques in this study are by interview and documentation. The data analysis technique used is qualitative and quantitative descriptive analysis. The results of this study are that the quality of e-filing services in South Malang KPP Pratama has been very good, the effectiveness of using e-filing based on effective Personal Taxpayer data is still not effective because there are still significant differences with the submission of Annual Tax Returns manually but already has increased every year, the target and realization of submission of Annual Tax Returns for Individual Taxpayers using e-filing has been achieved well and continues to increase for each year. DOI: 10.26905/ap.v6i1.380210.26905/ap.v6i1.380210.26905/ap.v6i1.380210.26905/ap.v6i1.380210.26905/ap.v6i1.380210.26905/ap.v6i1.3802